2014
DOI: 10.1074/jbc.m114.569889
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TBL1XR1 Disrupts Glucocorticoid Receptor Recruitment to Chromatin and Results in Glucocorticoid Resistance in a B-Lymphoblastic Leukemia Model

Abstract: Background:Resistance to glucocorticoid agonists is a major challenge in the treatment of pediatric leukemia. Results: TBL1XR1 knockdown decreases glucocorticoid signaling and response in leukemia cells. Conclusion:Deletions in TBL1XR1 at relapse may drive resistance to glucocorticoid agonists. Significance: Identifying drivers of glucocorticoid resistance in leukemia may allow for the identification of novel therapies for the treatment of recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 45 publications
(59 reference statements)
0
47
0
Order By: Relevance
“…Recurrent mutations or deletions have been identified in 19% of primary central nervous system lymphoma cases, Sezary syndrome, and 2/9 ABC-type DLBCLs [3942]. TBL1XR1 disrupts glucocorticoid receptor recruitment to the chromatin and results in glucocorticoid resistance in B-ALL [43]. Our study revealed that TBL1XR1 mutation at the WD40 domain facilitates binding with NCoR , leading to increased degradation of the NCoR complex, which results in activation of the NF-κB and c-Jun pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent mutations or deletions have been identified in 19% of primary central nervous system lymphoma cases, Sezary syndrome, and 2/9 ABC-type DLBCLs [3942]. TBL1XR1 disrupts glucocorticoid receptor recruitment to the chromatin and results in glucocorticoid resistance in B-ALL [43]. Our study revealed that TBL1XR1 mutation at the WD40 domain facilitates binding with NCoR , leading to increased degradation of the NCoR complex, which results in activation of the NF-κB and c-Jun pathways.…”
Section: Discussionmentioning
confidence: 99%
“…GR is subject to various post-translational modifications , which can mediate subcellular trafficking, promoter specificity, cofactor interaction, receptor stability, and turnover [152]. At specific gene loci, the response to glucocorticoids is regulated by the recruitment of cofactors, which can act in varying mechanisms, including: remodeling the chromatin, facilitating the assembly of transcriptional machinery, or modifying histones or other components of the transcription factor complex [153156]. These coregulators of GR function maintain tissue-specific expression [157, 158].…”
Section: Figurementioning
confidence: 99%
“…Viral preparation, genome-wide shRNA screening, 17 real-time quantitative polymerase chain reaction, 18 apoptosis assays, 18 cell viability assays, 18 immunoblots, 18 phospho flow cytometry, 19 and xenograft models [20][21][22][23] were all performed as previously described with additional details and modifications available in the supplemental Methods, found on the Blood Web site.…”
Section: Additional Methodsmentioning
confidence: 99%